Communicating with children and adolescents : action for change - Bannister, Anne; Huntington, Annie, 1962- (Jessica Kingsley Publishers, 2002)
At a time when expectations and assumptions about the delivery of services to children and adolescents are being reconfigured - for example, around the rights of children and adolescents as young citizens - adults are seeking to ensure that they deliver services in creative and empowering ways, ensuring that the opinions of young people are actively solicited and encouraged. Action methods - communication methods using the body as well as speech - provide non-threatening ways of communicating which can be understood by children of all ages and from many cultures. This book places action method.
Keywords: Interpersonal communication in children.; Interpersonal communication in adolescence.; Children and adults.; Parent and teenager.; Drama -- Therapeutic use.; Children.; Social service.; Psychodrama; Adolescent; Child; Social Work; Communication interpersonnelle chez l'enfant.; Communication interpersonnelle chez l'adolescent.; Enfants et adultes.; Parents et adolescents.; Psychodrame.; Enfants.; Service social.; children (people by age group); POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare.; POLITICAL SCIENCE -- Public Policy -- Social Security.; Social service; Drama -- Therapeutic use; Children; Children and adults; Interpersonal communication in adolescence; Interpersonal communication in children; Parent and teenager